anonymous
  • anonymous
Solve System, any help would be greatly appreciated. {x+y+z=3 x+y-z 2x-3y+z=-1
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
whpalmer4
  • whpalmer4
\[x+y+z=3\]\[x+y-z = ???\]\[2x-3y+z=-1\] What's the right hand side of the second equation?
anonymous
  • anonymous
=9
anonymous
  • anonymous
{x+y+z=3 x+y-z=9 2x-3y+z=-1

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

whpalmer4
  • whpalmer4
\[x+y+z=3\]\[x+y-z=9\]\[2x-3y+z=-1\] I would observe that adding the first two equations will eliminate \(z\). Can you see another way to add or subtraction equations or multiples thereof to eliminate \(z\)?
anonymous
  • anonymous
-3y-(y1+y2)??
whpalmer4
  • whpalmer4
how about adding the second and third equations? \(z\) has coefficients which are equal in magnitude but opposite in sign... So what do you get if you add the first and second equations together? What about the second and third equations?
anonymous
  • anonymous
Im sorry add them how as in Factor?
whpalmer4
  • whpalmer4
No, just add them like columns of numbers: \[x+y+z=3\]\[x+y-z=9\]-------------\[2x+2y+0z=12\]
whpalmer4
  • whpalmer4
See how the \(z\) term vanished?
whpalmer4
  • whpalmer4
Do that with another combination, so you get two new equations in terms only of \(x, y\).
whpalmer4
  • whpalmer4
Then we'll do the same process again, to get an equation in terms of just one of the variables, which we solve. With the value of that variable in hand, we work backwards to find the other variables.
anonymous
  • anonymous
k just a sec
anonymous
  • anonymous
so i got to get x and y =0?
whpalmer4
  • whpalmer4
No. What do you get if you add the second and third equations in the manner that I did with the first two?
anonymous
  • anonymous
2x-3y+z=-1 x+ y- z= 9 3x-2y+0x=8
whpalmer4
  • whpalmer4
Let me try again. Here I'll add the first two equations: \[x+y+z=3\]\[x+y-z=9\]-------------\[2x+2y+0z=12\] Now I'll add the last two equations: \[x+y-z=9\]\[2x-3y+z=-1\]------------------\[3x-2y+0z=8\] Now I have a system of 2 equations in 2 unknowns: \[2x+2y=12\]\[3x-2y=8\] Add those together, and what do you get?
anonymous
  • anonymous
-x+0y=4
whpalmer4
  • whpalmer4
\[2x+2y=12\]\[3x-2y=8\]------------\[5x=20\]\[x=\] Now use the known value of \(x\) in one of the two equations you just added to find \(y\).
anonymous
  • anonymous
x=4
anonymous
  • anonymous
I do not get this so x=4 but it is asking me to solve for y and z.... so how do i get those? Also i apologize Im really dull with these....
whpalmer4
  • whpalmer4
Okay, you know that \(x=4\). You also know that \(2x+2y=12\) and \(3x-2y=8\). Plug \(x=4\) into one of those two equations and solve for \(y\).
anonymous
  • anonymous
y=4
whpalmer4
  • whpalmer4
Let's use the first one. \[2x+2y=12\]\[2(4)+2y=12\]\[8+2y=12\]\[2y=12-8\]\[2y=4\]\[y=2\] Now check using the other equation: \[3(4)-2(2) = 8\]\[12-4=8\checkmark\] So, we now know \(x=4\) and \(y=2\).
whpalmer4
  • whpalmer4
Use one of the original equations + those two values to find \(z\).
anonymous
  • anonymous
2x-3y+z=-1 2(4)-3(2)+z=1 8-6+z=-1 2+z=-1 z=-3
whpalmer4
  • whpalmer4
Okay, now you need to try those 3 values in each of the original equations and make sure they are all correct. It is not sufficient to try just one or two of the equations.
whpalmer4
  • whpalmer4
Of course, if one of them turns out to be incorrect, you don't have to try the rest!
texaschic101
  • texaschic101
good job @whpalmer4 .....you did it again......patience is a virtue
anonymous
  • anonymous
dang i think i got it....
anonymous
  • anonymous
God thank you so much for bearing with me.... and thank so much for helping me understand.
whpalmer4
  • whpalmer4
I'm a little worried that you don't seem to grasp the concept of adding the equations together. You can add them (like we did), you can subtract them (I prefer adding, few mistakes with - signs!), and you can also multiply an equation by a number before adding or subtracting. For example, you can subtract by multiplying one of the equations by -1, then adding. Practice with this stuff helps! And remember (especially when learning) to check ALL of the equations when you think you have a solution...
texaschic101
  • texaschic101
he is good isn't he....he should be a teacher :)
whpalmer4
  • whpalmer4
Glad I could help! but now it's time to go watch a movie :-)
anonymous
  • anonymous
enjoy it sir and have a wonderful day.

Looking for something else?

Not the answer you are looking for? Search for more explanations.